Detection mechanism of an autonomous vehicle: Self recognising obstructions - Chung, Wye Kit; Po, Jiang Ling*; Adib Kabir, Chowdhury (IEEE, 2016)
An autonomous vehicle (AV) is coined as a term that signifies a vehicle that can be operated with minimal or zero human intervention. The adverts of our technologies have made this possible and is foreseen to be made publicly available in the near future. The realization of this technology comes together with the abilities of sensors to analyze data regarding its surrounding environment and communicating it to the `brain' or microcontroller of the autonomous vehicle. Thus, the objective of this paper is to simulate the situation when an autonomous vehicle comes near an obstruction particularly a pothole. In this paper, we propose a detection mechanism for an AV to self-recognize obstructions by utilizing light sensors.